A Bird in Hand: An Examination of the Influence of Nursing School Proximal Density on Hospital Quality of Care Outcomes in U.S. Hospitals. (27th April 2022) - Haun, Courtney N.; Silvera, Geoffrey A.
While nurse staffing shortage is generally true, it is not universal, and it remains unclear the degree to which variation in local staffing markets might influence the relationship between nurse staffing and care quality. This study seeks to determine the effect of nurse staffing markets on the quality of hospital care delivered in U.S. hospitals by examining the relationship between the proximal density of nurse staffing resources to hospitals and patient-reported care quality outcomes. This examination analyzes hospital performance on (Hospital Consumer Assessment of Healthcare Providers and Systems) HCAHPS based on the proximal density of nursing schools. The analysis combines data from Centers for Medicare and Medicaid Services (CMS) Hospital Compare (N1 = 2959) and U.S. nursing school locations from the American Association of Colleges of Nursing (N2 = 811) via a series of binary logistic regressions to determine whether local nurse staffing availability is related to hospital's attainment of either low or high star quality ratings. A sensitivity analysis is also offered to determine the association with 1, 3, and 5-star ratings. The findings suggest that the odds of receiving both a low-star rating and a high-star rating of HCAHPS performance increase as proximal density increases while the odds of receiving a 3-star rating decrease. Hospitals are able to achieve the highest levels of performance as high performing hospitals in high-density markets seem to be taking advantage of resource availability to establish close, strong ties with nurse staffing resources as opposed to viewing nurses as an easily replaceable resource.